Reconceptualizing opportunity construct: An answer to a theoretical dilemma through a systematic literature review (2021)
After Shane’s seminal work in 2000 which highlighted the importance of entrepreneurial opportunities, the number of studies focusing on entrepreneurial opportunity increased rapidly. Different definitions of this concept were provided in the field, ranging from subjective to objective ones, which gave rise to a lack of consensus among researchers and this, in turn, was an obstacle that slowed down theorizing in entrepreneurship. Taking into account the past trends in management sciences, it seems to be the right moment to re-conceptualize the core construct of opportunity. The major critique of existing definitions is their operationalization. To provide a better operationalization, the present study aimed to offer a more accurate conceptual definition. To this end, the study first examined current debates on opportunity, which revealed the major problem causing the debates. Then, through a systematic literature review, from among more than seven thousand documents in the Scopus database containing opportunity keywords, 74 papers were selected following different phases of filtration. The papers were analyzed in detail to extract different constructs. Then, using the framework of Hansen et al, they were classified along six dimensions. The concepts under each dimension were examined to finally provide a bigger picture of the construct of opportunity and offer a re-conceptualization. The results of this study highlight the gaps for future research and pave the ground for other systematic literature reviews in the field.